2022
DOI: 10.12775/rf.2022.008
|View full text |Cite
|
Sign up to set email alerts
|

Sprzeciw sumienia w zawodzie farmaceuty. Badanie opinii farmaceutów na temat klauzuli sumienia

Abstract: Streszczenie   Klauzula sumienia została wprowadzona do obszaru prawnych regulacji międzynarodowych w związku z uchwałą Rady Europy o nr 1763 z dnia 7 października 2010 r. Zgodnie z treścią dokumentu istnieje przyzwolenie odstąpienia od wykonania określonego świadczenia medycznego ze względu na zastrzeżenia moralne (religijne lub światopoglądowe) zgłaszane przez przedstawicieli opieki zdrowotnej.  W przepisach polskiego prawa medycznego powołanie się na zasadę klauzuli sumienia jest dozwolone, ale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Baranowska and colleagues demonstrated that pharmacists are more likely to refuse to grant the right to CC to their fellow pharmacists [ 41 ]. Finally, Czekajewska, Langer and Baum showed that, according to pharmacists, invoking the CC would hinder patients’ rightful access to various pharmaceutical services, undermine their trust in HCPs and generate moral conflicts with other employees and patients [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Baranowska and colleagues demonstrated that pharmacists are more likely to refuse to grant the right to CC to their fellow pharmacists [ 41 ]. Finally, Czekajewska, Langer and Baum showed that, according to pharmacists, invoking the CC would hinder patients’ rightful access to various pharmaceutical services, undermine their trust in HCPs and generate moral conflicts with other employees and patients [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the court's decision Poland was ordered to pay 61,000 euros. services, undermine their trust in HCPs and generate moral conflicts with other employees and patients [12].…”
Section: Pharmacists N (%N) P For Groups Differencesmentioning
confidence: 99%
See 2 more Smart Citations